World Health Organization Estimates of the Global and Regional Disease Burden of Foodborne Diseases, 2010 - Torgerson, Paul (2017)
Presentation by Paul Torgerson, Food Safety Workshop 24 May 2017. This was presented at the workshop "Better Targeting Food Safety Investments in Low and Middle Income Countries," hosted by A4NH and LSHTM.